c.2 - "Gupta, R. K." (New Delhi, 1996)
This book deals with the methods of learning Astrology, casting and analysing the horoscopes from all angles. The book deals with Hindu Astrology. At places the notions, nomenclature of planets and sign terminology etc. have been tabulated for facility of the readers. Chapter 10 is a ready reckoner for analysing any horoscope with planets anywhere in the birth chart for each ascendant.In this work, the basis f Hindu Astrology have been expounded in part 1, where specific chapters have been laid down on Shad Vargas which normally are not available in other books. The importance of Nakshatras has been detailed in a separate Chapter. Transit of planets, Dasa System analysis, Female Horoscopy are other specialized chapters of this book. The book has been prescribed as Text book for students of Astrology in the course of Astrology at Bharatiya Vidya Bhawan, New Delhi where the subject is being taught in collaboration with Indian Council of Astrological Sciences.
Keywords: Astrology